LEGISLATIVE PROBLEM OF EXCLUDING A PARTNER FROM THE COMPANY ON THE EXAMPLE OF GEORGIA (COMPARATIVE ANALYSIS) - Ketevan Kokrashvili; Lasha Gorgadze (International Journal of Innovative Technologies in Social Science, 2021)
The issue of excluding a partner (removing a partner) from the company is one of the most important, very sensitive and controversial issues in corporate law. The legislation of different countries regulates this issue in different ways, but it is important that most countries, together with the decision of the General Meeting of Partners, to exclude a partner, require a relevant court decision that has entered into legal force. On the basis of a comparative analysis, the presented article discusses the possible reasons for the exclusion of a partner and the issues of legal regulation of the exclusion procedure. The fiduciary duties of a partner are analyzed as one of the important reasons for the exclusion of a partner from the company. Special attention is paid to legislative gaps and to the heterogeneity of the case law of Georgia in connection with the exclusion of a partner from the company. However, the article discusses the shortcomings of the new draft law of Georgia on Entrepreneurs, it is worth mentioning that the draft law was developed on the basis of the Association Agreement between Georgia and the European Union. Under this agreement, Georgia undertook an obligation to integrate Georgian corporate law into EU corporate law, in addition, in our opinion, the positions presented in the article will significantly develop and improve such an important institution of corporate law as the exclusion of a partner from the company.